﻿Revalidation of Passalites Gloger, 1841 for the Amazon brown brocket deer P.nemorivagus (Cuvier, 1817) (Mammalia, Artiodactyla, Cervidae) - Morales-Donoso, Jorge Alfonso; Vacari, Gabrielle Queiroz; Bernegossi, Agda Maria; Sandoval, Eluzai Dinai Pinto; Peres, Pedro Henrique Faria; Galindo, David Javier; de Thoisy, Benoit; Vozdova, Miluse; Kubickova, Svatava; Barbanti Duarte, José Mauricio (ZooKeys, 2023)
Mazamanemorivaga (Cuvier, 1817) is a gray brocket deer that inhabits the Amazon region. An assessment of previous studies revealed inconsistencies in its current taxonomic classification, suggesting the need for an update in its genus classification. A taxonomic repositioning of this species is proposed through the collection of a specimen from its type locality (French Guiana) with subsequent morphological (coloring pattern, body measurements, and craniometry), cytogenetics (G Band, C Band, conventional Giemsa, Ag-NOR staining, and BAC probe mapping), and molecular phylogenetic analysis (mitochondrial genes Cyt B of 920 bp, COI I of 658 bp, D-loop 610 bp), and comparisons with other specimens of the same taxon, as well as other Neotropical deer species. The morphological and cytogenetic differences between this and other Neotropical Cervidae confirm the taxon as a unique and valid species. The phylogenetic analysis evidenced the basal position of the M.nemorivaga specimens within the Blastocerina clade. This shows early diversification and wide divergence from the other species, suggesting that the taxon should be transferred to a different genus. A taxonomic update of the genus name is proposed through the validation of Passalites Gloger, 1841, with Passalitesnemorivagus (Cuvier, 1817) as the type species. Future research should focus on evaluating the potential existence of other species within the genus Passalites, as suggested in the literature.
Keywords: taxonomy; new genus; Cervidae; Mazamanemorivaga; brocket deer